Figures of youth: on the very object of Youth Studies. (2nd July 2020) - Threadgold, Steven
ABSTRACT: 'Youth' as a social category is used and abused in all manner of ways across an array of fields, platforms, discourses and spaces, Youth Studies notwithstanding. When we talk about 'young people' sometimes we seem to be referring to different phenomena, depending upon our political interests, theoretical perspectives and research methods. This article interrogates how the concept of 'youth' is figuratively put to work. By suggesting different figures of youth, and inviting suggestions for more, I propose that tracing how they are situated in different ontological spaces can develop a clearer conception of our research object(s) and help reduce confusion and the possibility that we are talking past each other. The incomplete picture I want to paint of figures of youth, in quite broad-brush strokes, all inter-relate in something of a feedback loop, a material-semiotic assemblage that forms powerful affects for the ways that 'youth' is brought into being, how youth are researched, governed, co-opted and exploited.